Endovascular embolization of tentorial dural arteriovenous fistulas (EMBOTENT): a retrospective multicenter study - Vollherbst, Dominik F.; Krug, Nadja; Zhang, Peng; Ma, Yongjie; Su, Xin; Limbucci, Nicola; Renieri, Leonardo; Mosimann, Pascal J.; Boutet, Alexandre; Cheng, How-Chung; Marnat, Gaultier; Barreau, Xavier; et al. (BMJ, 2026)
Background Tentorial dural arteriovenous fistulas (TDAVFs) are rare but high risk vascular lesions. Although endovascular embolization is often the preferred treatment, large scale data on efficacy and safety are limited.
Objective To investigate the efficacy and safety of endovascular treatment for TDAVFs in a large, retrospective, multicenter cohort, and to analyze lesion characteristics and outcomes according to TDAVF location.
Methods Clinical, radiological, and interventional data from 585 patients treated in 32 international centers in 758 endovascular treatment sessions between 2012 and 2022 were analyzed. Patient demographics, fistula characteristics, endovascular treatment techniques, complications, and outcomes were assessed. Efficacy was measured by occlusion rates, safety by symptomatic complications, and modified Rankin Scale (mRS) scores.
Results In 31.3% of cases TDAVFs initially presented with hemorrhage, including 12.8% in low grade TDAVFs (absence of cortical venous reflux). Transarterial embolization was the primary approach in 84.7% of sessions. Complete occlusion was achieved in 74.2% of cases after the last treatment and 85.7% at the last imaging follow-up (mean 20.9 months). Symptomatic complications occurred in 9.4% of patients, with 2.6% permanent deficits and 1.0% mortality. At the last clinical follow-up (mean 30.6 months), 89.2% of patients had good functional outcome (mRS score 0–2). Location was significantly associated with fistula grade (eg, galenic and tentorial sinus TDAVFs being more often high grade, and torcular TDAVFs being more often low-grade).
Conclusions This large multicenter series demonstrated high occlusion rates, favorable functional outcomes, and acceptable complication rates, supporting endovascular therapy as a treatment of choice for TDAVFs. Considerable hemorrhage rates in low grade TDAVFs support the treatment even in the absence of cortical venous reflux.